Teaching the nation's past: Irish history in secondary schools, 1924-1969 - MAC GEARAILT, COLM (Trinity College Dublin. School of Histories & Humanities. Discipline of History, 2019)
This thesis considers the teaching of Irish history in Irish secondary schools post-Independence. It analyses the version(s) of the past set for study, taught in schools, and learned by students in the Irish Free State and beyond. It tracks history as a subject, and specifically Irish history within this, from 1924, when the Department of Education was first founded, until 1969. It contends that a narrative of Irish history was promoted in secondary schools which tended to focus on a traditional ‘Great Man’ approach to history with a strong emphasis on high politics, and on religion. This narrative was not as simplistic however as previously assumed. By taking the differing emphases in the major textbooks into account, and appreciating how the Certificate examinations were not solely focused on promoting a militant version of Irish Catholic history, it challenges the received understanding of Irish history as taught in secondary schools during the period under investigation. As part of its investigation, it examines three key research questions: Firstly, what Irish history was taught, how it was taught, and why? Secondly, what cultural and political ideologies influenced the teaching of Irish history during this period? Finally, how did policy and official rhetoric relate to practice, and the reality of history at school-level. This study examines the curriculum set by the Department, how this developed over time, alongside the political, contextual and social forces which shaped these developments during this period. It also features the first comprehensive breakdown of the Certificate examination questions, which, as demonstrated in Chapters 5-7, increasingly dictated classroom teaching throughout the period. Moreover, the in-depth analysis conducted in Chapter 4 of the main school textbooks allows previously made claims to be quantifiably measured, and provides the most detailed examination of the Irish history school textbooks in use between 1921 and 1969 heretofore completed. This thesis also analyses issues of policy versus practice, moving beyond history as officially prescribed, and onto it as a subject in and of itself, in schools of all denominations. It highlights the official rhetoric as to Irish history’s purpose and importance, before considering this against the classroom realities, and the constrained context in which teaching occurred. It analyses issues of textbook production and usage, Church-State relations, policies relating to the Irish language, and teacher training and methods.
APPROVED
Keywords: History education,; Irish history teaching; Textbooks; Examinations; Teacher Training; Curriculum; Nation-state; Historiography